Proteases com atividade colagenolíticas produzidas por bacillus spp de solo amazônico - Lima , Lorena Azevedo de (2013)
Application of collagenolytic proteases has major importance in medical and industrial activity, with the most varied applications, as far in therapeutic scope as biotechnological. Collagenolytic proteases can hydrolyze both native collagen as denatured collagen, becoming increasingly commercially important. Among the various sources of collagenolytic proteases, the microbial proteases show an important role in biotechnological processes. This study proposed to select samples of Bacillus sp. isolated from soil, those which showed the best production of collagenolytic proteases and characterize the enzyme. For selection of bacteria protease producer, eight samples from Bacillus sp. were reactivated in Mueller-Hinton broth and plated on Agar gelatin/milk 1 % (w/v). To determine the protease collagenolytic activity, bacteria were plated on solid medium with insoluble collagen 0.25 % (w/v) substratum. The colonies that showed hyaline halo of degradation were subjected to biochemical tests to confirm the taxonomy. Two successive 23 full factorial design with four replications at the center point were prepared for analysis of tracks of pH, temperature and substrate concentration. Eight samples reactivated, two had protease collagenolytic activity. The most collagenolytic activity of Bacillus sp. was 86.27 U / mL with specific activity 145.18 U / mg at pH 9.0 at 37 ° C with 1.5% (w / v) substrate concentration. Maximum collagenolytic enzyme activity of Bacillus stearothermophilus was 79,38 U / mL with specific activity of 136.92 U / mg at pH 7.2 at 25 ° C with substrate concentration of 1% (w / v). Both enzymatic extracts were optimally active at pH 9.0 at 50 ° C, remained stable in the range of alkaline pH and temperatures between 45 to 60 ° C. The results showed that the production of collagenolytic enzymes by Bacillus sp. DPUA 1728 and B. stearothermophilus DPUA 1729 have potential biotechnological.